Essential Role of STAT3 Signaling in Hair Follicle Homeostasis - Miyauchi, Kosuke; Ki, Sewon; Ukai, Masao; Suzuki, Yoshie; Inoue, Kentaro; Suda, Wataru; Matsui, Takeshi; Ito, Yoshihiro; Honda, Kenya; Koseki, Haruhiko; Ohara, Osamu; Tanaka, Reiko J.; et al. (Frontiers in Immunology, 2021)
Dominant-negative mutations associated with signal transducer and activator of transcription 3 (STAT3) signaling, which controls epithelial proliferation in various tissues, lead to atopic dermatitis in hyper IgE syndrome. This dermatitis is thought to be attributed to defects in STAT3 signaling in type 17 helper T cell　specification. However, the role of STAT3 signaling in skin epithelial cells remains unclear. We found that STAT3 signaling in keratinocytes is required to maintain skin homeostasis by negatively controlling the expression of hair follicle-specific keratin genes. These expression patterns correlated with the onset of dermatitis, which was observed in specific pathogen-free conditions but not in germ-free conditions, suggesting the involvement of Toll-like receptor-mediated inflammatory responses. Thus, our study suggests that STAT3-dependent gene expression in keratinocytes plays a critical role in maintaining the homeostasis of skin, which is constantly exposed to microorganisms.